Patterned Assembly of Quantum Dots onto Surfaces Modified with Click Microcontact Printing. (19th October 2012) - Gassensmith, Jeremiah J.; Erne, Petra M.; Paxton, Walter F.; Frasconi, Marco; Donakowski, Martin D.; Stoddart, J. Fraser
<x xml:space="preserve">Abstract</x> The self‐assembly of CdSe quantum dots (QDs) onto a patterned silica surface generated from surface microcontact click printing is presented. The mechanically robust self‐assembly process produces patterns of QDs which remain steadfast, even as subsequent reactions are performed on the substrate, demonstrating the utility and ease of this self‐assembly process. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>